CONSIDERATION OF HEALTH INDICATORS IN PHYSICAL EDUCATION (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
The development of any society is comprehensively determined by the healthy generation, as well as the potential of manpower. Therefore, First president I.A.Karimov "...the issue of bringing the spiritual and physical harmonious generation to an adult is a national, universal task for us, and I would like to reiterate that the consistent and resolute continuation of our work carried out for this noble purpose is the focus of our today's policy" he stressed, especially in the field of education. Thanks to the consistent reforms in the education system of our country, the realization of the young generation's mind, physical ability, talent, healthy and harmonious upbringing paved the way to the physical perfection of the owners of our country sooner. The goal is to bring our children's physical development and physical training closer to the level of developed countries of the world in this regard.